Wearable logo‐antenna for GPS–GSM‐based tracking systems. Issue 12 (1st September 2016) - Monti, Giuseppina; Corchia, Laura; De Benedetto, Egidio; Tarricone, Luciano
Abstract : This study presents a wearable antenna for a global positioning system–global system for mobile communication (GPS–GSM)‐based anti‐theft tracking system to be embedded in high‐cost clothing and luggage accessories (such as leather bags). To assess the feasibility of this solution, a prototype antenna was designed mimicking the shape of one of the Levi Strauss & Co.'s logos, and it was fabricated using a conductive non‐woven fabric on a layer of leather. Furthermore, to cover both the GPS L1 and the GSM‐1800 bands with a single radiating element, positive‐intrinsic‐negative (PIN) diodes were employed to reconfigure the operating frequency of the antenna. Experimental data demonstrating the feasibility of the proposed design strategy are presented and discussed.